Literature and science - Ruston, Sharon (Essays and studies (London, England : 1950), 2008)
"In 1959 C.P. Snow memorably described the 'gulf of mutual incomprehension' which existed between 'literary intellectuals' and scientists, referring to them as 'two cultures'. This volume looks at the extent to which this has changed. Ranging from the middle ages to twentieth-century science fiction and literary theory, and using different texts, genres, and methodologies, the essays collected here demonstrate the complexity of literature, science, and the interfaces between them."--Jacket.